2012
DOI: 10.1128/mcb.05722-11
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Role for Copper in Ras/Mitogen-Activated Protein Kinase Signaling

Abstract: c Copper (Cu) is essential for development and proliferation, yet the cellular requirements for Cu in these processes are not well defined. We report that Cu plays an unanticipated role in the mitogen-activated protein (MAP) kinase pathway. Ablation of the Ctr1 high-affinity Cu transporter in flies and mouse cells, mutation of Ctr1, and Cu chelators all reduce the ability of the MAP kinase kinase Mek1 to phosphorylate the MAP kinase Erk. Moreover, mice bearing a cardiac-tissue-specific knockout of Ctr1 are def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
223
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(239 citation statements)
references
References 65 publications
13
223
0
3
Order By: Relevance
“…However, the intracellular localization of Ctr1, found in PC-3, although unable to promote the redistribution of circulating copper, may promote its sequestration in intracellular compartments and facilitate the dissociation of the 64 Cu-ATSM complex. Finally, whereas the study of copper transport distribution does not explain the differences in tracer uptake, it does highlight a need for greater understanding of the role of copper in cell proliferation and of the involvement of transporters in the resistance and in the toxicity of platinum derivatives (36,37). 64 Cu-ATSM at 2 h, and 64 Cu-ATSM at 24 h after injection in the same mouse.…”
Section: Discussionmentioning
confidence: 99%
“…However, the intracellular localization of Ctr1, found in PC-3, although unable to promote the redistribution of circulating copper, may promote its sequestration in intracellular compartments and facilitate the dissociation of the 64 Cu-ATSM complex. Finally, whereas the study of copper transport distribution does not explain the differences in tracer uptake, it does highlight a need for greater understanding of the role of copper in cell proliferation and of the involvement of transporters in the resistance and in the toxicity of platinum derivatives (36,37). 64 Cu-ATSM at 2 h, and 64 Cu-ATSM at 24 h after injection in the same mouse.…”
Section: Discussionmentioning
confidence: 99%
“…Foundational studies by Thiele and co-workers in fly and mouse cell models led to the discovery that copper is required for MEK1/2 activity (81). Biochemical characterization demonstrated that copper binds directly to purified MEK1/2, facilitating phosphorylation of recombinant ERK1/2 in vitro; conversely, copper chelation inhibits ERK1/2 phosphorylation in vitro (81). Elegant work by Brady et al showed the physiological importance of this copper-MAPK connection in a cancer setting.…”
Section: Controlling Cancer With Labile Coppermentioning
confidence: 99%
“…Recently, it has been reported that copper is a required cofactor for the kinase activity of MEK1 (34,35). We hypothesized that glutathione inhibits MEK1 activity through chelating copper.…”
Section: Glutathione Activates Foxo3 By Chelating Copper To Inhibit Mekmentioning
confidence: 99%